Esthetic effect of the buccal corridor size and amount of tooth-gingival display on smile attractiveness in two student population - Hooman Zarif Najafi; Morteza Oshagh; Mohsen Azizi (Tehran University of Medical Sciences, 2015)
3- Dentist   Background and Aims: An attractive, well-balanced smile is a paramount treatment objective of the modern orthodontic therapy. The purpose of this study was to determine the effects of the buccal corridor size and tooth-gingival display on the smile esthetics as perceived by two groups of the students.   Materials and Methods: A colored image of a woman frontal posed smile was selected. The image was altered digitally to produce different buccal corridor sizes (6%, 12.5% and 20%) and different tooth-gingival displays (maxillary central incisors and 2 mm of gingival, maxillary central incisors and dental papilla and 80% of the maxillary central incisors). The different buccal corridor sizes and tooth-gingival displays were combined to produce 9 images. These altered images were rated by 120 medical and dental students using Visual Analogue Scale (VAS). Data were analyzed using Mann-Whitney test, Pairwise comparison LSD test, Repeated measure MANOVA and ICC (Intraclass Correlation Coefficient).   Results: The smile which had the buccal corridor size of 12.5% and complete incisor display without gingival display received the highest rates among the nine smile images in the dental students group. But in the medical students group the smile with the buccal corridor size of 12.5% and 2 mm gingival display, received the highest rates among the nine smile images. There was no significant difference in judging between the male and female raters for the both groups (P>0.05). The dental students were more critical about the increasing of the gingival display.   Conclusion: In the treatment procedure that may lead to the combination of wide buccal corridor and more tooth-gingival show, more caution should be considered.